THE EFFECT OF ADDITION OF CANTHAXANTHIN IN FEED TO INCREASE THE VISUAL VIEW OF COMET FISH, Carassius auratus (Linnaeus, 1758) - Septiyani, Eka Sary; Yudha, Indra Gumay; Elisdiana, Yeni (University of Lampung, 2020)
One effort made to improve the color quality of comet fish is to add canthaxanthin. Canthaxanthin is a red-orange pigment found in plants, fungi, bacteria, crustaceans, sea trout, and algae. This study aims to determine the optimum dose of canthaxanthin given in feed to improve comet fish' color quality. This research is also expected to be beneficial for fish farmers related to the use of canthaxanthin to improve comet fish' color quality. This study used 5 treatments with 3 replications. This research was conducted in April-June 2019 at the Aquaculture Laboratory, Department of Fisheries and Marines, University of Lampung. The parameters observed were color measurement using the Red Blue Green (RGB) method, converted into the Hue Saturation Brightness (HSB) value, color measurement by the scoring method, and water quality. The addition of canthaxanthin in diets with different doses showed the highest results in treatment C (P <0.05) on comet fish visual appearance. The results showed that the best dose in this study was the addition of canthaxanthin as much as 125 mg/kg of feed.